The European Union democratic deficit and the public sphere : an evaluation of EU media policy - Ward, David (Informatization developments and the public sphere, 2002)
An assessment of EU communications policy judged against democratic and normative criteria within the framework of the question of the need for a European-wide public sphere. It argues that the EU should proceed through the mass media, with a policy based on a public service philosophy.